Association of aortic wall thickness on contrast-enhanced chest CT with major cerebro-cardiac events. (November 2014) - Tresoldi, Silvia; Di Leo, Giovanni; Zoffoli, Elena; Munari, Alice; Primolevo, Alessandra; Cornalba, Gianpaolo; Sardanelli, Francesco
Background: There is a significant association between aortic atherosclerosis and previous major cardiovascular events. Particularly, thoracic aortic atherosclerosis is closely related to the degree of coronary and carotid artery disease. Thus, there is a rationale for screening the thoracic aorta in patients who undergo a chest computed tomography (CT) for any clinical question, in order to detect patients at increased risk of cerebro-cardiovascular (CCV) events. Purpose: To estimate the association between either thoracic aortic wall thickness (AWT) or aortic total calcium score (ATCS) and CCV events. Material and Methods: One hundred and forty-eight non-cardiac patients (78 men; 67±12 years) underwent chest contrast-enhanced multidetector CT (MDCT). The AWT was measured at the level of the left atrium (AWTref ) and at the maximum AWT (AWTmax ). Correlation with clinical CCV patients' history was estimated. The value of AWTmax and of a semi-quantitative ATCS as a marker for CCV events was assessed using receiver-operating characteristic curve (ROC) analysis and multivariate regression analysis. Results: Out of 148 patients, 59% reported sedentary lifestyle, 44% hypertension, 32% smoking, 23% hypercholesterolemia, 13% family history of cardiac disease, 12% diabetes, and 10% BMI ≥30 kg/m 2 ; 9% reported myocardial infarction, 8% aortic aneurism, 8% myocardial revascularization, and 2% ischemic stroke. Twenty-six percent of patients had a medium-to-high ATCS. Both AWTmax and AWTref correlated with hypertension and age ( P  < 0.002). At the ROC analysis, a 4.8 mm threshold was associated to a 90% specificity and an odds ratio of 6.3 (AUC = 0.735). Assuming as threshold the AWTmax median value (4.3 mm) of patients who suffered from at least one CCV event in their history, a negative predictive value of 90%, a RR of 3.6 and an OR of 6.3 were found. At the multivariate regression analysis, AWTmax was the only independent variable associated to the frequency of CCV events. Conclusion: Patients with increased thoracic AWTmax on chest MDCT could be considered at risk for CCV disease.